Eye Closure Interacts with Music to Influence Vividness and Content of Directed Imagery. (December 2022) - Herff, Steffen A.; McConnell, Sophie; Ji, Julie L.; Prince, Jon B.
Goal-directed, intentional mental imagery generation supports a range of daily self-regulatory activities, such as planning, decision-making, and recreational escapism. Many clinical interventions for mood and anxiety disorders also use imagery and their effectiveness can be affected by an individual's ability to manipulate vividness and content of mental imagery. Prior literature points towards music as a promising candidate to influence imagination in such settings, but basic questions remain regarding how music affects mental imagery and how it interacts with basic, well-established parameters, such as facilitatory effects of eye closure. One hundred participants listened to music and a silent control whilst performing a guided mental imagery task. Specifically, participants saw a short video of a figure journeying towards a landmark and imagined a continuation of the journey with either closed or open eyes. After each trial, participants reported vividness and content of their imagined journeys. Bayesian Mixed Effects Models obtained strong evidence of greater vividness, duration, as well as distance travelled in music conditions compared to silent conditions. Additionally, interactive effects of music and eye closure were found for both vividness and the emotional valence of imagined content, where music effects were disproportionately amplified by eye closure. Findings further support music's potential to manipulate the perceptual, spatial-temporal, as well as emotional sentiment of deliberately generated mental imagery.